Economic burden of pertussis in children: A single-center analysis in Hangzhou, China - Liu, Yan; Yang, Yingying; Zhou, Jinsi; Zhang, Xuechao; Gu, Lintao; Xu, Yuyang; Lu, Zhaojun; Xie, Qixin; Zhang, Xiaoping; Hua, Chunzhen (Human vaccines & immunotherapeutics, 2024)
The "reemergence of pertussis" has elicited international concerns, occurring paradoxically amidst the expansion of immunization programs. This study was aimed to evaluate quantitatively the economic burden and identify the determinants that influence the cost associated with treating pertussis in Chinese children. We evaluated the economic burden by Chinese children diagnosed with pertussis at the Children's Hospital, Zhejiang University School of Medicine in 2022. Direct medical expenses and the utilization of medical resources attributed to pertussis were calculated. A generalized linear regression model was applied to analyze the determinants that were associated with the direct medical expenses among patients. Among the 1110 pertussis patients included in the study, 1060 were outpatients and 50 were inpatients. The average direct medical cost was ¥1878.70(i.e. $279.33). Living in urban areas (OR:1.27, p = .04), complications (OR:1.40, p < .001), hospitalization (OR:10.04, p < .001), and ≥ 3 medical visits (OR:3.71, p < .001) were associated with increased direct medical expenses. Having received four doses of the pertussis vaccine was associated with reduced direct medical expenses (OR:0.81, p = .04). This study underscores a substantial economic burden of pertussis in Hangzhou, with pronounced implications for patients residing in urban areas, experiencing complications, requiring hospitalization, having multiple medical consultations, or lacking comprehensive pertussis vaccination.